2021
DOI: 10.53487/ataunisosbil.971183
|View full text |Cite
|
Sign up to set email alerts
|

Eğitim Fakültesi Öğrencilerinin E-Öğrenmeye Yönelik Tutumlarının İncelenmesi

Abstract: Araştırmada, veri toplama ve analiz süreçlerinde nicel araştırma tasarımlarından betimsel tarama modeli kullanılmıştır. Araştırmada lisans ve yüksek lisans öğrencilerinin çoğunluğunun erişimini evindeki bilgisayar ve telefondan karşıladığı görülmüştür. Elektronik cihaz kullanma düzeyi çok yeterli ve yeterli olan öğrencilerin memnuniyet ve teknoloji kullanma eğilimlerinin yüksek olduğu görülmüştür. Yüksek lisans öğrencilerinin lisans öğrencilerine göre e-öğrenmeden memnuniyet ve motivasyon ortalamalarının daha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
4
0
5
Order By: Relevance
“…Considering that the highest score that can be obtained from the scale is 92, it can be put forward that Turkish teacher candidates' attitudes towards e-learning are at the medium level. In previous studies, Bahadır (2021) and Barış (2015) found that students' attitudes towards e-learning are low; Haznedar (2012), Durmuş and Kaya (2010), Yağcı, Alsancak Sarıkaya and Özüdoğru (2015) found as "moderate"; Yakar and Yıldırım Yakar (2021) found as "low" close to the moderate; Şahin (2021), Şimşek, İskenderoğlu and İskenderoğlu (2010) found that they are "indecisive"; Dikbaş (2006) found as "positive"; Kar, Saha and Mondal (2014) found it as "high". These studies revealed that students' attitudes towards e-learning are at different levels.…”
Section: Result Discussion and Suggestionsmentioning
confidence: 91%
See 1 more Smart Citation
“…Considering that the highest score that can be obtained from the scale is 92, it can be put forward that Turkish teacher candidates' attitudes towards e-learning are at the medium level. In previous studies, Bahadır (2021) and Barış (2015) found that students' attitudes towards e-learning are low; Haznedar (2012), Durmuş and Kaya (2010), Yağcı, Alsancak Sarıkaya and Özüdoğru (2015) found as "moderate"; Yakar and Yıldırım Yakar (2021) found as "low" close to the moderate; Şahin (2021), Şimşek, İskenderoğlu and İskenderoğlu (2010) found that they are "indecisive"; Dikbaş (2006) found as "positive"; Kar, Saha and Mondal (2014) found it as "high". These studies revealed that students' attitudes towards e-learning are at different levels.…”
Section: Result Discussion and Suggestionsmentioning
confidence: 91%
“…This finding shows that there is no relationship between attitude towards e-learning and academic achievement and between attitude towards e-learning and digital literacy. Bahadır (2021), in his study conducted with education faculty students, unfolded that the relationships between students' attitudes towards e-learning and their achievement are very low. Similarly, Barış (2015) stated that students' attitudes towards e-learning are low, while Abbasi, Ayoob, and Memon (2020) expressed that students' attitudes towards e-learning were negative.…”
Section: Result Discussion and Suggestionsmentioning
confidence: 99%
“…Emotional maturity is also necessary for healthy human relationships and better communication in addition to adequate use of the body. Emotional maturity is defined as the individual's ability to understand one's own emotions and to regulate them in a way that can improve his/ her life level and to empathize with others' emotions [2,3]. Today, communication has become a tool that individuals at all levels and in all professions should maintain technical knowledge thereof and adequately develop their skills [4].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, at the end of 2019, in the pandemic process experienced around the world, many countries decided to close schools for a certain period of time, and an urgent distance education process was launched. All teachers working in private and public schools in Turkey also had to apply the assessment and evaluation processes online (Ada et al, 2021;Altunçekiç, 2021;Sezgin, 2021). The transition to the urgent distance education process in the country increased the importance of analyzing the readiness and habits of teachers and students, especially regarding e-assessment and evaluation (Bozkurt, 2020;Shraim, 2019;Telli & Altun, 2020).…”
Section: Introductionmentioning
confidence: 99%